Research on key parameters of pipeline transportation of waste rock treatment in underground residual space - Gu, Wenzhe; Zhu, Lei; Song, Tianqi (Frontiers in Earth Science, 2023)
As the key link of coal gangue slurry filling, slurry pipeline transportation is an important guarantee to realize the slurry mixing and safe transportation of gangue from solid powder. To realize the underground excavation gangue of the Huangling No. 2 coal mine without raising the ground, the slurry filling technology is proposed to transport the slurry made by gangue through the pipeline and fill it into the goaf. The phase composition and microstructure characteristics of underground excavation gangue in the Huangling No. 2 coal mine were analyzed by X-ray diffraction and an electron microscope scanning test, the slurry-forming properties of gangue powder with different particle sizes and gradations were studied, and the influence of gangue slurry concentration on its rheological properties was analyzed. The experimental results show that the gangue powder crushed using a cage crusher can be made into stable slurry when the particle grading size is the natural crushing gradation with the upper limit of particle size less than 3 mm. The viscosity of the slurry is positively correlated with the concentration. When the concentration is below 70%, the increase in viscosity is small, and when the concentration is above 70%, the increase in viscosity is significant. It is determined that the concentration of the Huangling No. 2 coal mine slurry is 70%. Based on the determination of slurry preparation parameters, the simulation analysis of slurry pipeline transportation was carried out, the influence of design velocity on the velocity distribution of the pipeline section and the variation law of slurry concentration was explored, and the design velocity of the project is determined to be 1.5 m/s. The engineering practice shows that the slurry preparation parameters are reasonable. The crushing and pulping of gangue under the ground and the safe transportation of a 6 km pipeline are realized, which provides a reference for similar engineering projects.